Influence of water coupling coefficient on the blasting effect of red sandstone specimens - Yang Li; Renshu Yang; Yanbing Wang; Dairui Fu (International Journal of Coal Science & Technology, 2024)
Abstract This study investigates the impact of different water coupling coefficients on the blasting effect of red sandstone. The analysis is based on the theories of detonation wave and elastic wave, focusing on the variation in wall pressure of the blasting holes. Using DDNP explosive as the explosive load, blasting tests were conducted on red sandstone specimens with four different water coupling coefficients: 1.20, 1.33, 1.50, and 2.00. The study examines the morphologies of the rock specimens after blasting under these different water coupling coefficients. Additionally, the fractal dimensions of the surface cracks resulting from the blasting were calculated to provide a quantitative evaluation of the extent of rock damage. CT scanning and 3D reconstruction were performed on the post-blasting specimens to visually depict the extent of damage and fractures within the rock. Additionally, the volume fractal dimension and damage degree of the post-blasting specimens are calculated. The findings are then combined with numerical simulation to facilitate auxiliary analysis. The results demonstrate that an increase in the water coupling coefficient leads to a reduction in the peak pressure on the hole wall and the crushing zone, enabling more of the explosion energy to be utilized for crack propagation following the explosion. The specimens exhibited distinct failure patterns, resulting in corresponding changes in fractal dimensions. The simulated pore wall pressure–time curve validated the derived theoretical results, whereas the stress cloud map and explosion energy-time curve demonstrated the buffering effect of the water medium. As the water coupling coefficient increases, the buffering effect of the water medium becomes increasingly prominent.